“Things which don’t shift and grow are dead things”: Revisiting Betonie’s Waste-Lands in Leslie Silko’s Ceremony - Brígido-Corachán, Anna M. (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2014)
This article explores the socio-political background that led to widespread Native American urban relocation in the period following World War II – a historical episode which is featured in Leslie Marmon Silko’s acclaimed novel Ceremony (1977). Through an analysis of the recycling, reinterpreting practices carried out by one of Ceremony’s memorable supporting characters, Navajo healer Betonie, Silko’s political aim to interrogate the state of things and to re-value Native traditions in a context of ongoing relations of coloniality is made most clear. In Silko’s novel, Betonie acts as an organic intellectual who is able to identify and challenge the 1950s neocolonial structure that forced Native American communities to either embrace hegemonic practices and lifestyles or else be condemned to cultural reification and abject poverty. Through his waste-collecting and recycling activities, Betonie develops alternative solutions that go beyond a merely spiritual or epistemological dimension of life and materially intervene in the social text. The margins of 1950s urban sprawl functioned as repositories of indigenous cultural and intellectual capital that was being consciously, actively transformed by Native agents such as him. Thus, through Ceremony’s medicine man, Leslie Silko criticizes disempowering attitudes of victimhood and Native self-shame while vindicating indigenous historical territories and unconventional political strategies. She also anticipates the liminal practices of material and cultural recycling we see in countless Western cities today, in the aftermath of the most recent world economic crisis.